2016
DOI: 10.1007/s11096-016-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

The need for community pharmacists in oncology outpatient care: a systematic review

Abstract: Background One-third of all deaths in Europe each year are attributable to cancer. Issues relating to cancer care, therefore, will continue to expand. To manage the increased challenges-including doctor shortages, an ageing population, and rural distribution of supplies-community pharmacists will likely be required to assume responsibility within oncology care. Aim of the review To assess the need for further investigation into quantity and utility of community pharmacists' interventions in assisting oncology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Our results indicated that there are few studies on this topic, with most of them being published from 2015. This is consistent with a current systematic review of pharmacist intervention models in oncology, which indicates that most research in this area is focused on inpatients . In addition, most studies were conducted in the United States, Europe and Asia.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results indicated that there are few studies on this topic, with most of them being published from 2015. This is consistent with a current systematic review of pharmacist intervention models in oncology, which indicates that most research in this area is focused on inpatients . In addition, most studies were conducted in the United States, Europe and Asia.…”
Section: Discussionsupporting
confidence: 88%
“…A previous systematic review explored the role of pharmacists in communicating to people living with cancer about their use of complementary medicines, whereas another review assessed models of pharmacist interventions in assisting oncology patients. However, to the best our knowledge, summarized evidence on the effect of pharmacist interventions in outpatients with cancer is lacking in the current literature.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacists' expert pharmaceutical knowledge and broad skill set -coupled with their widespread accessibility and trusted relationships with patients and carers -mean that they are well suited to better integration within the palliative care team [22], [25] . The pharmacist's role is extending beyond the more traditional elements of dispensing activity and management of minor ailments towards the provision of greater psychosocial support for patients [22], [26] . This creates opportunities for further interaction, not only with patients, but also with loved ones, relatives and carers.…”
Section: Role Of the Pharmacist In Palliative Carementioning
confidence: 99%
“…This is an increasingly relevant topic in light of pharmacists' involvement in palliative care services both nationally and globally [21], [22], [23], [24], [25], [26] .…”
mentioning
confidence: 99%